Efficacy of a Plasmodium vivax malaria vaccine using ChAd63 and modified vaccinia Ankara expressing thrombospondin-related anonymous protein as assessed with transgenic Plasmodium berghei parasites. - Bauza, K; Malinauskas, T; Pfander, C; Anar, B; Jones, E; Billker, O; Hill, A; Reyes-Sandoval, A (2014)
Plasmodium vivax is the world's most widely distributed malaria parasite and a potential cause of morbidity and mortality for approximately 2.85 billion people living mainly in Southeast Asia and Latin America. Despite this dramatic burden, very few vaccines have been assessed in humans. The clinically relevant vectors modified vaccinia virus Ankara (MVA) and the chimpanzee adenovirus ChAd63 are promising delivery systems for malaria vaccines due to their safety profiles and proven ability to induce protective immune responses against Plasmodium falciparum thrombospondin-related anonymous protein (TRAP) in clinical trials. Here, we describe the development of new recombinant ChAd63 and MVA vectors expressing P. vivax TRAP (PvTRAP) and show their ability to induce high antibody titers and T cell responses in mice. In addition, we report a novel way of assessing the efficacy of new candidate vaccines against P. vivax using a fully infectious transgenic Plasmodium berghei parasite expressing P. vivax TRAP to allow studies of vaccine efficacy and protective mechanisms in rodents. Using this model, we found that both CD8+ T cells and antibodies mediated protection against malaria using virus-vectored vaccines. Our data indicate that ChAd63 and MVA expressing PvTRAP are good preerythrocytic-stage vaccine candidates with potential for future clinical application.